2014
DOI: 10.1073/pnas.1321187111
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of the A20/ABIN-mediated inhibition of NF-κB signaling via modifying the ubiquitinated proteins in a basal chordate

Abstract: In the past decade, ubiquitination has been well documented to have multifaceted roles in regulating NF-κB activation in mammals. However, its function, especially how deubiquitinating enzymes balance the NF-κB activation, remains largely elusive in invertebrates. Investigating bbtA20 and its binding proteins, bbt A20-binding inhibitor of NF-κB (bbtABIN1) and bbtABIN2, in Chinese amphioxus Branchiostoma belcheri tsingtauense, we found that bbtABIN2 can colocalize and compete with bbt TNF receptor-associated fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…In contrast, we did not find a homologous A20 sequence in the genomes of lower invertebrates including Drosophila . Similar to mammalian cells, and as shown here for zebrafish, A20 expression in amphioxus is also regulated by LPS 19,45 and A20 modulates NF-κB signalling utilizing a ubiquitin editing function 13,21,45 . However, the in vivo functional significance of A20 in amphioxus has not been tested 45 .…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In contrast, we did not find a homologous A20 sequence in the genomes of lower invertebrates including Drosophila . Similar to mammalian cells, and as shown here for zebrafish, A20 expression in amphioxus is also regulated by LPS 19,45 and A20 modulates NF-κB signalling utilizing a ubiquitin editing function 13,21,45 . However, the in vivo functional significance of A20 in amphioxus has not been tested 45 .…”
Section: Discussionsupporting
confidence: 63%
“…Similar to mammalian cells, and as shown here for zebrafish, A20 expression in amphioxus is also regulated by LPS 19,45 and A20 modulates NF-κB signalling utilizing a ubiquitin editing function 13,21,45 . However, the in vivo functional significance of A20 in amphioxus has not been tested 45 . Reminiscent of mouse data 1,9 , we found that A20 deficiency in zebrafish was lethal and remarkably re-introduction of human A20 could rescue a proportion of A20-deficient zebrafish from lethality.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Because of its A20-binding capacity, it is frequently assumed that ABIN-1's functions involve A20 (17,31,32). Indeed, ABIN-1 coexpression with A20 was shown to induce destabilization of the IKK complex and inhibition of NF-kB signaling in a lower chordate model organism (33). Similarly, ABIN-1 cooperates with A20 to inhibit antiviral signaling or TNF-regulated NF-kB signaling (20,34).…”
Section: Discussionmentioning
confidence: 99%
“…Amphioxus SARM plays inhibitory roles in both MyD88-and TICAM-dependent pathways by interacting with MyD88, TRAF6, and TICAM (19,21). Recently, ubiquitination was shown to be essential in regulating the activation of amphioxus NF-kB (22,23). In addition to these TIR adaptors having homologies with their vertebrate counterparts, most amphioxus TIR adaptors exhibit novel protein domain architectures, such as the TIR domain linked with the kinase domain and the TIR domain linked with the caspase recruitment domain (CARD).…”
mentioning
confidence: 99%